Constitutional Law: Implikasi Bentuk Negara, Bentuk Pemerintahan dan Sistem Pemerintahan Terhadap Sistem Bernegara Latvia - Yunus, Nur Rohim (BULETIN ADALAH, 2021)
Latvia is a democratic nation located in Northern Europe that operates under a parliamentary republican style of governance. Latvia, as a unitary state, exhibits a centralized distribution of government power, with its capital located in Riga. The Republic of Latvia operates under a republican form of government, wherein the executive authority is wielded by the prime minister and his cabinet, who are accountable to the parliament, known as the Saeima. The president, in their capacity as the chief executive, assumes a ceremonial and diplomatic function, having been chosen by the Saeima for a designated duration of service. The governmental structure of Latvia exhibits a harmonious equilibrium between legislative and executive authority, wherein the parliament assumes the principal role in enacting legislation and overseeing the government, while the prime minister assumes responsibility for the day-to-day administration. The role of the President in Latvia's national unity and exterior relations is of symbolic significance. The Republic of Latvia exhibits a robust parliamentary democracy characterized by a well-balanced framework of government institutions, as evidenced by its form of state, form of government, and system of governance.